The collaborative sale : solution selling in a buyer-driven world - Eades, Keith M. (Wiley, 2014)
"Buyer behavior has changed the marketplace, and sellers must adapt to surviveThe Collaborative Sale: Solution Selling in Today's Customer-Driven World is the definitive guide to the new reality of sales. The roles of buyers, sellers, and technology have changed, and collaboration is now the key to success on all sides. The Collaborative Sale guides sales professionals toward alignment with buyers, by helping them overcome their problems and challenges, and creating value. From building a robust opportunity pipeline and predicting future revenues to mastering the nuances of buyer conversations, the book contains the information sales professionals need to remain relevant in today's sales environment. Buyers have become more informed and more empowered. As a result, most sellers now enter the buying process at a much later stage than the traditional norm. The rise of information access has given buyers more control over their purchases than ever before, and sellers must adapt to survive. The Collaborative Sale provides a roadmap for adapting through sales collaboration, detailing the foundations, personae, and reality of the new marketplace. The book provides insight into the new buyer thought processes, the new sales personae required for dealing with the new buyers, and how to establish and implement a dynamic sales process. Topics include: Selling in times of economic uncertainty, broad information access, and new buyer behavior Why collaboration is so important to the new buyers The emergence of new sales personae - Micro-marketer, Visualizer, and Value Driver Buyer alignment, risk mitigation, and the myth of control Situational fluency, and the role of technology Focused sales enablement, and buyer-aligned learning and development Implementation and establishment of a dynamic sales process The book describes the essential competencies for collaborative selling, and provides indispensable supplemental tools for implementation. Written by recognized authorities with insights into global markets, The Collaborative Sale: Solution Selling in Today's Customer-Driven World is the essential resource for today's sales professional"--